Pathologies of imagination and affectivity: the genesis of the unconscious in Marc Richir - Senatore, Mauro (Frontiers in Psychiatry, 2023)
In their recent work in phenomenological psychopathology, Andreas Rosén Rasmussen and Joseph Parnas argue that there is an expressive relationship between the anomalies of imagination reported in schizophrenic spectrum disorders (SSD) and an underlying generative self- or ipseity-disorder. They build their argument on an updated review of the phenomenological model of consciousness, by which each experience articulates itself in ipseity according to its modality. Therefore, they explain imagination as the figuration of an absent object mediated by the imaginary and accompanied by a sense of irreality. Finally, by drawing on patients’ descriptions, Rasmussen and Parnas show that SSD imagination disorders testify to the breakdown of this model of consciousness. In this article, I aim to complexify the scenario summarized above by focusing on the contribution made by the phenomenologist Marc Richir in his late masterwork Phantasia, imagination et affectivité (2004). To this end, I examine the genetic analyses of the pathologies of the imaginary that Richir develops through a non-standard interpretation of Husserl’s phenomenology of imagination (in particular, Hua XXIII, text n.16, 1912). In my examination, I aim to unfold an alternative model of consciousness that (a) is based on the gap between the architectonic registers of phantasia and imagination (and the corresponding stages of sense-making and the institution of sense), (b) takes account of the role of affectivity in those registers, (c) places the pathologies of the imaginary in the quasi-empathy that characterizes the missed encounter with the other, (d) links the institution of these pathologies with the psychoanalytic account of the fixation of the phantasm.